CD8 T cells are dispensable for experimental autoimmune prostatitis induction and chronic pelvic pain development - Salazar, Florencia C.; Martinez, Maria S.; Paira, Daniela A.; Chocobar, Yair A.; Olivera, Carolina; Godoy, Gloria J.; Acosta-Rodriguez, Eva V.; Rivero, Virginia E.; Motrich, Ruben D. (Frontiers in Immunology, 2024)
Chronic Pelvic Pain Syndrome or Chronic Prostatitis (CPPS/CP) is the most prevalent urologic affliction among young adult men. It is a challenging condition to treat, which significantly decreases patient quality of life, mostly because of its still uncertain aetiology. In that regard, an autoimmune origin is a prominent supported theory. Indeed, studies in patients and in rodent models of Experimental Autoimmune Prostatitis (EAP) have provided compelling evidence suggesting a key role of CD4 Th1 cells in disease pathogenesis. However, the implication of other prominent effectors of the immune system, such as CD8 T cells, has yet to be studied. Thus, we herein analysed the induction of prostatitis and the development of chronic pelvic pain in EAP using CD8 T celldeficient animals. We found similarly elevated PA-specific immune responses, with high frequencies of specific IFNgamma+CD4+ and IL17+CD4+ T cells in prostate draining lymph nodes from PAimmunised either CD8 KO or wild type animals with respect to controls. Moreover, these peripheral immune responses were paralleled by the development of significant chronic pelvic pain, and accompanied by prostate histological lesions, characterized by haemorrhage, epithelial cell desquamation, marked periglandular leukocyte infiltration, and increased collagen deposition in both, PA-immunised CD8 KO and wild type animals. As expected, control animals did not develop prostate histological lesions. Our results indicate that CD8 T cells do not play a major role in EAP pathogenesis and chronic pelvic pain development. Moreover, our results corroborate the previous notion that a CD4 Th1 associated immune response drives the induction of prostate tissue inflammation and the development of chronic pelvic pain.